1996
DOI: 10.1111/j.1432-1033.1996.0704p.x
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathway Associated with Stimulation of CB2 Peripheral Cannabinoid Receptor

Abstract: Cannabinoids, known for their psychoactive effects, also possess iminunomodulatory properties. The recent isolation and cloning of the G-protein-coupled peripheral cannabinoid receptor (CB2), mainly expressed in immune tissues, have provided molecular tools to determine how cannabinoid compounds may mediate immunomodulation. We here investigated the CB2 signaling properties using stably transfected Chinese hamster ovary cells expressing human CB2. First, we showed that stimulation by a cannabinoid agonist acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
192
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(210 citation statements)
references
References 38 publications
6
192
0
4
Order By: Relevance
“…Cannabinoids have previously been reported to activate ERK1/2 in various dierent cell types (Bouaboula et al, 1996;Wartmann et al, 1995), and in the present study we observed that the time course of the cannabinoid-induced inhibition of gap junction coupling was mirrored by the phosphorylation of Cx43, which was the most predominant connexin expressed in the endothelial cells studied. Both the incorporation of 32 P into Cx43 as well as its mobility shift in SDS ± PAGE were prevented by MEK inhibitors which also prevent the cannabinoid-induced activation of ERK1/2.…”
supporting
confidence: 61%
“…Cannabinoids have previously been reported to activate ERK1/2 in various dierent cell types (Bouaboula et al, 1996;Wartmann et al, 1995), and in the present study we observed that the time course of the cannabinoid-induced inhibition of gap junction coupling was mirrored by the phosphorylation of Cx43, which was the most predominant connexin expressed in the endothelial cells studied. Both the incorporation of 32 P into Cx43 as well as its mobility shift in SDS ± PAGE were prevented by MEK inhibitors which also prevent the cannabinoid-induced activation of ERK1/2.…”
supporting
confidence: 61%
“…However, the susceptibility of DCs from Bid-KO mice to THC-induced apoptosis suggested that Bid was dispensable in THC-induced apoptosis. The CB1 and CB2 are G-protein-coupled receptors that are linked to a variety of signaling pathways including the cAMP pathway (28) and MAPK pathway (29,30) in a PTX-sensitive manner. In addition, it was shown that THC-induced apoptosis in malignant glioma induce sustained ceramide accumulation and Raf/extracellular signal regulated kinase activation (21).…”
Section: Discussionmentioning
confidence: 99%
“…22]. Specifically, it has been demonstrated that retention of c-fos in the cytoplasm is controlled by a labile transport inhibitor, which itself can be inhibited by cAMP [23]. Therefore, to determine whether CBN inhibited nuclear translocation of these proteins, a comparison between nuclear and cytosolic protein expression of c-fos and c-jun was performed by Western analysis.…”
Section: Effect Of Cbn On Nuclear Translocation Of C-fos and C-jun Prmentioning
confidence: 99%